THE EFFECT OF BORON AND IAA APPLIED TO SUNFLOWER GROWED AS A SECOND PRODUCT ON SEED SETTING - Gölkaya, Samet; Tamkoç, Ahmet (JOURNAL OF ADVANCES IN AGRICULTURE, 2023)
This research was carried out on the second crop oil sunflower, which was planted directly on the stubble in the Central Anatolia region. Increasing doses of boron (4.2 gr, 8.5 gr, and 16.8 gr) and increasing doses of IAA (12 ppm, 16 ppm, and 20 ppm) were applied to leaves of sunflower at R2 and R3 development stages of sunflower in order to increase the number of full seeds (Pieces/Capitulum) of the second crop oil sunflower. The data obtained from the experiment with 4 replications were evaluated statistically, and the difference between them was significant at the p<0.05 probability level. However, the difference between the potential seed number (Pieces/Capitulum) was insignificant. While 4.2 gr and 8.5 gr boron doses from the boron doses applied plots and 20 ppm IAA dose from the IAA applied plots had the highest grain yields, the lowest seed setting was observed in the 16.8 gr boron applied plots and the 12 ppm and 16 ppm IAA applied plots. It has been concluded that the IAA used in the research has both positive and negative effects on productivity against stress conditions created by environmental factors.